Influence of polarization and misalignment on the signal of a trap detector - Machekhin, Yu. P.; Kohns, P.; Krasnogorov, A. (ННЦ «Институт метрологии», 2003)
Modem development of many branches of a science and engineering puts increased require¬ments to accuracy of measurement of power of laser radiation in a wide range of frequencies and power. There is a significant need for precise measurement of absolute value of power from a source of radiation in the optical region with a low or uitralow level of power (from several a milli¬watt up to units of nanowalt and less).
Keywords: polarization; trap detector